Tourism management an introduction - Inkson, Clare; Minnaert, Lynn (Los Angeles SAGE, 2018)
This text offers a concise introduction to all the core topics of tourism management. Covering both key theory and practice, it introduces general management issues across the whole tourism sector, focusing particularly on the challenges of managing tourism in the 21st century.
Part I: Tourism Overview -- Chapter 1. Introduction -- Chapter 2. Understanding Tourism -- Part II: Tourism Supply and Demand -- Chapter 3. Tourist Generating Regions -- Chapter 4. Tourism Demand -- Chapter 5. Tourism Suppliers -- Chapter 6. Intermediaries in the Tourism System -- Part III: Tourism Impacts -- Chapter 7. The Economic Impacts of Tourism -- Chapter 8. The Social and Cultural Impacts of Tourism -- Chapter 9. The Environmental Impacts of Tourism -- Part IV: Tourism Management and Marketing -- Chapter 10. Destination Development and Management -- Chapter 11. Tourism Marketing -- Chapter 12. The Management of Visitors -- Chapter 13. Public Sector Involvement in Tourism -- Part V: Tourism Ahead -- Chapter 14. Tourism and the Future.
Includes bibliographical references and index.
Keywords: Tourism; Tourism -- Management